Faktor Penyebab Pembuangan Bayi Di Kota Kupang, Nusa Tenggara Timur Dalam Perspektif Kriminologi - Wahye Elisabeth Hunga; Josef Mario Monteiro; Jenny Ermalinda (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This research is motivated by baby abandonment, a form of crime against children still found in Kupang City. It demonstrates that this act is influenced not only by legal aspects but also by various criminological factors. This study aims to analyze the factors causing baby abandonment in Kupang City and analyze efforts to address it. The literature review in this study discusses the concept of criminology, crime from a criminological perspective, the basic concept of baby abandonment, types and forms of baby abandonment, criminological theories including Strain Theory, Labeling Theory, Rational Choice Theory, and Social Control Theory, the factors underlying baby abandonment, and a humanistic legal approach through preemptive, preventive, repressive, and restorative justice efforts as the basis for the research analysis. This study uses empirical legal research methods with criminological, sociological, and restorative approaches. Data were obtained through interviews, observations, and literature review with four respondents, then analyzed qualitatively. The results of the study indicate that baby abandonment in Kupang City is influenced by three main factors: psychological factors, social factors, and family environmental factors. Psychological factors include fear, panic, shame, emotional stress, and depression due to unwanted pregnancy. Social factors include the societal stigma against premarital pregnancy and a lack of support from partners and the community. Family environmental factors are characterized by harsh parenting styles, weak communication, and a lack of parental supervision. Mitigation efforts are carried out through pre-emptive, preventive, and repressive approaches, but their implementation is not optimal due to the limited synergy between families, communities, and law enforcement officials. Based on the results of the study, it can be concluded that baby abandonment is a crime influenced by various interrelated factors, so that its handling is not sufficient through law enforcement alone, but also requires an integrated psychological, social, and family approach. Therefore, increased education, strengthening the role of families, and cooperation between agencies are needed to prevent the recurrence of the crime of baby abandonment in Kupang City.